Line scan images of IODP Hole 386-M0083F - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Collection of line scan images from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. Images were obtained during the onshore phase of the expedition, which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu. After longitudinal splitting high-resolution (100 pixels/cm) images of each core sections archive half was captured using the Tri-Sensor Core Logger (TSCL; NS Design). The camera provides a 16-bit red-green-blue color (48-bit) TIFF file, which were converted to JPG files for publication purposes. The RGB data derived from each image for each section are published under titles "Color data (RGB) of IODP Hole 386-M0083F". For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023